2020
DOI: 10.3390/jcm9092722
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Effectiveness of Calcium Silicate Sealers against a Nutrient-Stressed Multispecies Biofilm

Abstract: Purpose: This study compared the antimicrobial efficacy of calcium silicate sealers (BioRoot RCS and Total Fill BC) and conventional sealers (AH Plus and Tubli-seal) against planktonic bacteria and a nutrient-stressed multispecies biofilm. Methods: Antimicrobial properties of freshly mixed sealers were investigated using the direct contact test (DCT) and a nutrient-stressed multispecies biofilm comprised of five endodontic strains. Antimicrobial activity was determined using quantitative viable counts and conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 46 publications
0
6
0
4
Order By: Relevance
“…Além do teste de contato direto, as membranas foram utilizadas para simular a inacessibilidade dos cimentos aos microrganismos, testando a capacidade de difusão de seus componentes contra uma barreira física no teste de contato indireto (Barros, et al, 2014;Kapralos, et al, 2018;Viana, et al, 2021). Quando em contato direto, os cimentos biocerâmicos (Bio-C Sealer, Sealer Plus BC e BioRoot RCS) apresentaram melhor atividade (P < 0,05) contra biofilmes de E. faecalis do que os cimentos à base de resina (AH Plus, Sealer Plus, MTA Fillapex); estudos anteriores confirmam esses achados (Bukhari, et al, 2019;Alsubait, et al, 2019;Bose, et al, 2020). Bio-C Sealer exibiu potencial ação antimicrobiana quando comparado ao AH Plus.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Além do teste de contato direto, as membranas foram utilizadas para simular a inacessibilidade dos cimentos aos microrganismos, testando a capacidade de difusão de seus componentes contra uma barreira física no teste de contato indireto (Barros, et al, 2014;Kapralos, et al, 2018;Viana, et al, 2021). Quando em contato direto, os cimentos biocerâmicos (Bio-C Sealer, Sealer Plus BC e BioRoot RCS) apresentaram melhor atividade (P < 0,05) contra biofilmes de E. faecalis do que os cimentos à base de resina (AH Plus, Sealer Plus, MTA Fillapex); estudos anteriores confirmam esses achados (Bukhari, et al, 2019;Alsubait, et al, 2019;Bose, et al, 2020). Bio-C Sealer exibiu potencial ação antimicrobiana quando comparado ao AH Plus.…”
Section: Resultsunclassified
“…A eficácia antimicrobiana dos cimentos biocerâmicos foi avaliada em poucos estudos anteriores, utilizando diferentes métodos microbiológicos e obtendo diferentes resultados (Candeiro, et al, 2016;Bukhari & Karabucak, 2019;Alsubait, et al, 2019;Bose, et al, 2020;Barbosa, et al, 2020). Estudos recentes revelaram a mesma eficácia dos cimentos biocerâmicos e do Research, Society and Development, v. 10, n. 8, e52910817593, 2021 (CC BY 4. (Candeiro, et al, 2016;Barbosa, et al, 2020).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Another premixed calcium silicate sealer, TotalFill BC (FKG Swiss Endo, La Chauxde-Fonds, Switzerland), killed over 40% of E. faecalis biofilm in dentin [67], and showed effective antimicrobial properties against single-species [68] and multi-species endodontic biofilm using a direct contact test [69,70] and confocal laser scanning microscopy [71]. One recent study showed TotalFill BC had higher antimicrobial efficacy than AH-Plus sealer using a modified direct contact test [70].…”
Section: Premixed Bioceramic Sealersmentioning
confidence: 99%
“…Антибактериальные свойства биокерамического силера выражены существенно [35][36][37]. Высокие значения рН имеют особое значение для герметика корневых каналов, поскольку высвобождение ионов кальция стимулирует отложение твердых тканей и их антибактериальные свойства [22,36,[38][39][40].…”
Section: антибактериальные свойстваunclassified